Prevention and treatment of Clostridium perfringens epsilon toxin intoxication in mice with a neutralizing monoclonal antibody (c4D7) produced in Nicotiana benthamiana - Garcia, J.P. (2014)
Epsilon toxin (ETX), produced by Clostridium perfringens types B and D, is among the most lethal toxins known. ETX is a potential bioterrorism threat that was listed as a Category B agent by the U.S. Centers for Disease Control until 2012 and it still remains a toxin of interest for several government agencies. We produced a monoclonal antibody (MAb) against ETX (ETX MAb c4D7) in Nicotiana benthamiana and characterized its preventive and therapeutic efficacy in mice. The ETX preparation used was highly lethal for mice (LD(50) =1.6 μg/kg) and resulted in a mean time from inoculation to death of 18 and 180 minutes when administered intravenously or intraperitoneally, respectively. High lethal challenge resulted in dramatic increases of a variety of pro-inflammatory cytokines in serum, while lower, but still lethal doses, did not elicit such responses. ETX MAb c4D7 was highly effective prophylactically (ED(50) = 0.3 mg/kg; ED(100) = 0.8 mg/kg) and also provided protection when delivered 15-30 minutes post-ETX intoxication. These data suggest that ETX MAb c4D7 may have use as a pre- and post-exposure treatment for ETX intoxication.